PENGARUH TRANSPARANSI DAN PARTISIPASI MASYARAKAT DESA DALAM PENGELOLAAN KEUANGAN TERHADAP PEMBANGUNAN DESA (STUDI KASUS DI DESA BERINGIN, KECAMATAN SIBISA, KABUPATEN DAIRI) - DIAN GUSTRAZAIMAN PURBA TAMBAK (LP2MTBM MAKARIOZ, 2021)
Village development is slowly progressing little by little but even so there are still some damaged roads on the area toagriculture and uneven construction of residential roads. In the management of Village Finance, it is also necessary to knowthe village apparatus, Transparency, and Community Participation to support the growth of village development to achieve aprosperous and developing village. Infrastructure development of the road to agricultural areas must also be consideredbecause the majority of beringin village people are farming, if the road to agricultural area is damaged it will be difficult for thecommunity to be able to carry out their agricultural activities and it will also be more difficult if the harvest season arrives. Ifthe agricultural area road is not immediately repaired, of course, many people will complain and have difficulty in transportingtheir crops because the purpose of village development is one of them to meet the needs and prosper the community. Thestage in village development includes planning, implementation, and supervision. The implementation of village developmentis carried out by promoting togetherness, family, and unity to realize peace and social justice. In order for villagedevelopment to run well and produce, then village development must be planned, coordinated, time-limited, and inaccordance with the typical conditions of the community and the village area concerned and the active role of the community,village devices, village institutions, institutions at the subdistrict and district level.